FAKTOR YANG MEMPENGARUHI NILAI PEMEGANG SAHAM DENGAN DIMODERASI SET KESEMPATAN INVESTASI DAN DIVIDEN - Isti Ariyanti; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe research was aimed to analyzed the effect of free cash flow and funding decisions on shareholder value with investment opportunity sets and dividend as moderating variables. The research sample is property, real estate and building construction companies listed on the Indonesia Stock Exchange (IDX) from 2012-2017. Moderated regression analysis (MRA) was the analysis technique. This research used shareholder value as the dependent variable, and used free cash flow and funding decisions as the independent variable. Investment opportunity sets and dividend as the moderating variable. The output of this research shows that the F test, free cash flow variables, funding decisions, investment opportunity sets, dividend, free cash flow moderation with investment opportunity sets, moderating free cash flow with dividends, moderating funding decisions with investment opportunity sets, moderating funding decisions with dividends significantly influences shareholder value. In partial testing (t test), free cash flow variables, financial decisions and moderation of free cash flow with investment opportunity sets significantly positive effect on shareholder value, while moderating free cash flow with dividends, moderating funding decisions with investment opportunity set and moderation funding decisions with dividends don’t show the significant results.Keywords : Free cash flow, financing decisions, investment opportunity set, dividend, shareholder value.